School homework and its relationship with student academic achievement in Malaysia - Chew, F.P.; Teong, M.H.; Ishak, Z. (2012)
School homework has been synonymous with students’ life in Chinese national type primary schools in Malaysia. Although many reports in the press claimed that students were burdened with too much of it, homework continues to be a common practice in national type schools that is believed to contribute to academic achievement. This study is conducted to identify the relationship between the burden of school homework and academic achievement among pupils in Chinese National Type Primary School in the state of Perak, Malaysia. A total of 284 students (142 from urban and 142 from rural) respectively were chosen as participants in this study. Variables of gender and location (urban/rural areas) has shown significant difference in student academic achievement. Female Chinese student from rural areas showed a higher mean score than males from urban area. Therefore, the Chinese language teachers should give appropriate and relevant homework to primary school students to achieve good academic performance.